The Politics of Transnational Memory in Amy Tan’s The Joy Luck Club - Silvia Schultermandl (Journal of Transnational American Studies, 2011)
“The Politics of Transnational Memory in Amy Tan’s The Joy Luck Club” sees Tan’s representation of memory as either a function of loss (and limited recovery) or of distance (whether temporal or physical). For Schultermandl, the text suggests that familial or national relationships built on generational and immigrant memory cannot really create conditions of solidarity or identification and are thus doomed to failure—either that, or what is “memory” must be transformed by “experience” and then be understood, what Schultermandl calls “belated memory.” Schultermandl offers an account of the failure of the narrative to provide for a bond between the generations of women—immigrant mothers and American-born daughters. This conceptual problem is represented by the novel’s end, where the overriding implication of the narrative is that in order to reconcile and occupy the identity of a Chinese American one must somehow be both Chinese and American, an experience of being that Schultermandl questions. Additionally, in not representing modern China or modern Chinese women, Schultermandl argues, the novel gives up an opportunity to create a “transnational solidarity” among women in favor of a national identity that supersedes the individual, who in Tan’s text becomes a mere stand-in for traditionally held ideological and national stereotypes.